Incorporating the salient principles of Diyah in constructing a workable no-fault compensation system for medical injuries - Mohd Najid, Khadijah; Jahn Kassim, Puteri Nemie (IDOSI Publications, 2017)
The prevailing trend amongst many jurisdictions around the globe has moved towards adopting amicable systems in compensating victims of medical injuries. One of the main systems which have been widely debated and scrutinised on is the no-fault compensation system. In adopting this system, victims of medical injuries no longer require to prove ‘fault’ and therefore, negligence on the part of the medical provider. The fact that these victims have suffered injuries after seeking medical treatment triggers the system to automatically disburse fix levels of fund to compensate for the losses that they have suffered. The no-fault compensation system is thus, motivated by the principle of ‘distributive justice’, which highlights the role of society and community’s responsibilities. The basic features of a no-fault compensation system for medical injuries are therefore comparatively similar to the system of Diyah, whether in terms of principles as well as in its operation. While many studies on legal theory treat the system of Diyah as part of punishment in the realm of criminal law, in reality, the system of Diyah acts as a method of economic empowerment enabling the setup of a multidimensional welfare system in caring for the disadvantaged in the community. These shared values and similarities in principles and operation will be able to facilitate the harmonization between the two systems in an effort towards designing an ideal no-fault compensation system for medical injuries, which not only adheres to the Shariah, but suitable to be implemented in various local and international circumstances. Nevertheless, contemporary interpretation would be required to ensure that the dynamics of this Islamic compensation system is appropriately embraced in the age of globalisation.